High-dispersion flame-retardant master batch and preparation method thereof
By using composite flame retardant and modified nano calcium carbonate in polymer materials, combined with calcium-zinc stabilizer and lubricant, the problem of instability of traditional flame retardants affecting the mechanical properties and cost instability is solved, and high-dispersed flame retardant mother is achieved The efficient flame retardant and stability of the materials have promoted the wide application of polymer materials in many fields.
Patent Information
- Application Number
- CN202411631622.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-01-17
AI Technical Summary
When used in plastic products, traditional flame retardants will affect the mechanical properties, and will have unstable costs, poor color consistency, poor dispersion and processing difficulties, which limits the application of polymer materials in military, aerospace and other fields.
Using a high-dispersion flame retardant masterbatch, including polymers, composite flame retardants, plasticizers and additives, the composite flame retardant consists of antimony trioxide, borate and organic phosphorus nitrogen composites, and passes through high temperature reactions. The nano-calcium carbonate modified polycaprolactone is formed to improve the dispersion and stability of the flame retardant, and liquid and powder calcium-zinc stabilizers and metal soap lubricants are used to improve processing performance.
It significantly improves flame retardant performance and stability, reduces processing difficulty and cost, ensures consistency of product performance and long-term use performance, and is suitable for a variety of high-performance flame retardant materials needs.
Smart Images

Figure BDA0005136070190000181 
Figure BDA0005136070190000191 
Figure BDA0005136070190000201
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials and relates to a high-dispersion flame-retardant masterbatch and a preparation method thereof. Background Art
[0002] With the advancement of science and technology and the improvement of living standards, polymer materials such as plastics and rubber are becoming more and more important in people's lives, and their application scope is also showing a trend of expanding year by year. However, most organic polymer materials have different degrees of flammability in the air. The flammability of polymer materials brings very adverse effects, which not only involve safety and economy, but also include environment, society and health. This limits the application of polymer materials in many industries such as military, aerospace, transportation, electricity and civil use. Therefore, flame retardant modification of these materials has become an important research topic. The traditional flame retardant method is mainly to improve the fire resistance of materials by adding flame retardants. However, most flame retardants will affect the mechanical properties of the products when applied to plastic products, resulting in a decrease in mechanical properties (such as tensile strength, impact strength, etc.). At the same time, there are still problems such as poor dispersibility, difficult processing and large amount of dust causing pollution.
[0003] In order to solve the above problems, flame retardant masterbatch came into being. Flame retardant masterbatch is a concentrate prepared by dispersing flame retardants in carrier resins in high concentrations through special processes. This concentrate usually appears in granular or cake form. Flame retardant masterbatch generally includes flame retardants, carrier resins, additives, etc. The additives mainly include dispersants, stabilizers, lubricants, etc., which are used to improve the dispersibility and processing performance of flame retardants. Compared with the traditional addition of flame retardants, flame retardant masterbatch has the following advantages: by preparing flame retardant masterbatch, the dispersibility of flame retardants in resins can be improved, the amount of flame retardants added can be reduced, the processing difficulty and processing cost can be reduced, and the effect of the addition of flame retardants on the mechanical properties of resins can be reduced. After adding, it is not easy to have adverse phenomena such as stratification, patterns, and precipitation, which improves the working environment and saves manpower, material costs and time. Therefore, improving the processing technology of flame retardant resins through masterbatch technology has become a development trend in the industry.
[0004] Traditional flame retardant masterbatches mainly use antimony trioxide (Sb2O3) as a single flame retardant component. However, the price of antimony trioxide is affected by many factors, fluctuating greatly in recent years and continuing to rise. In addition, the hue of antimony trioxide in different mines is quite different, which has a great impact on the color consistency of downstream products. Therefore, it is urgent to find flame retardant masterbatches that can partially replace antimony trioxide, use composite materials to enhance the flame retardant properties of base fabrics, and reduce material costs while enhancing environmental protection and market competitiveness. In addition to having good flame retardant properties, flame retardant masterbatches used to manufacture plastic composites should also have good thermal stability, good processing dispersibility, little effect on the mechanical performance of products, and long-lasting flame retardant properties. By optimizing the formula and production process, a multi-functional flame retardant masterbatch is developed, which can not only solve many problems of existing flame retardants, but also meet the needs of different industries for high-performance flame retardant materials, and promote the widespread application of polymer materials in construction, electrical appliances, transportation, communications and other fields. Summary of the invention
[0005] The present invention aims at the deficiencies in the prior art and provides a masterbatch with high dispersion and excellent flame retardant effect.
[0006] One object of the present invention is achieved by the following technical solutions:
[0007] A highly dispersed flame retardant masterbatch comprises the following components in parts by weight: 8 to 30 parts of a high molecular polymer, 30 to 95 parts of a composite flame retardant, 6 to 20 parts of a plasticizer, and 0.1 to 15 parts of an auxiliary agent; the composite flame retardant comprises antimony trioxide, a borate, and an organic phosphorus-nitrogen complex, wherein the organic phosphorus-nitrogen complex is a mixture of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and melamine cyanurate, melamine phosphate, or one or more of ammonium polyphosphate.
[0008] Preferably, the composite flame retardant comprises a mixture of antimony trioxide, borate, and organic phosphorus-nitrogen complex in a mass ratio of 1:(0.5-1.0):(0.5-1.0).
[0009] Preferably, the organic phosphorus-nitrogen complex is a mixture of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and melamine cyanurate.
[0010] Preferably, the composite flame retardant comprises a mixture of antimony trioxide, borate, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and melamine cyanurate in a mass ratio of 1:(0.5-1.0):(0.3-0.6):(0.2-0.4).
[0011] Preferably, the composite flame retardant includes antimony trioxide, borate, organic phosphorus-nitrogen complex and metal hydroxide.
[0012] Preferably, the composite flame retardant includes antimony trioxide, borate, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, melamine cyanurate and metal hydroxide.
[0013] Preferably, the mass of the metal hydroxide is 0.1-10 wt % of the total mass of the composite flame retardant.
[0014] Preferably, the metal hydroxide is aluminum hydroxide and / or magnesium hydroxide.
[0015] Preferably, the borate is one or more of a metal salt of boric acid and a metal salt of fluoroboric acid, and the metal is one or more of sodium, potassium, magnesium, barium, ammonium, calcium, manganese, nickel, copper, aluminum, zinc, cobalt, and zirconium.
[0016] Preferably, the borate is one or more of calcium borate, cobalt borate, anhydrous zinc borate, 3.5 hydrate zinc borate, sodium orthoborate, sodium perborate, sodium metaborate, sodium tetraborate, ammonium metaborate, ammonium pentaborate, calcium metaborate, barium metaborate, barium tetraborate, potassium metaborate, potassium tetraborate, potassium pentaborate, magnesium orthoborate, magnesium metaborate, trimagnesium tetraborate, pentamagnesium tetraborate, potassium tetrafluoroborate, sodium tetrafluoroborate, ammonium tetrafluoroborate, zinc tetrafluoroborate, calcium tetrafluoroborate, magnesium tetrafluoroborate, and barium metaborate.
[0017] Preferably, the high molecular polymer is one or more of olefin polymers, ester polymers, vinyl polymers, styrene polymers, and polyurethane.
[0018] Preferably, the high molecular polymer is one or more of polyvinyl chloride, chloroacetic acid resin, and ethylene-vinyl acetate copolymer.
[0019] Preferably, the plasticizer is one or more of pyromellitic acid ester plasticizers, trimellitic acid ester plasticizers, phthalic acid ester plasticizers, terephthalic acid ester plasticizers, phosphate ester plasticizers, and epoxidized vegetable oil.
[0020] Preferably, the plasticizer is one or more of dioctyl phthalate, dinonyl phthalate, diisodecyl phthalate, diundecyl phthalate, didodecyl phthalate, ditridecyl phthalate, dioctyl terephthalate, tri(isopropylphenyl) phosphate, dialkyl tetrahalophthalate, tri(2-chloroethyl) phosphate, bisphenol A-bis(diphenyl phosphate), and epoxidized soybean oil.
[0021] Preferably, the auxiliary agent includes one or more of a dispersant, a stabilizer, and a lubricant.
[0022] Preferably, the dispersant is polycaprolactone-modified nano-calcium carbonate, and the amount of the dispersant is 0.1 to 4 parts.
[0023] Preferably, the stabilizer is a liquid calcium zinc stabilizer and a powdered calcium zinc stabilizer, and the amount of the stabilizer is 0.5 to 6.0 parts.
[0024] Preferably, the lubricant includes one or more of metal soap lubricants, hydrocarbon lubricants, fatty acid lubricants, and fatty acid ester lubricants, and the lubricant is 0.1 to 3 parts.
[0025] Preferably, the preparation method of the polycaprolactone-modified nano-calcium carbonate comprises the following steps:
[0026] The nano-calcium carbonate and polycaprolactone are put into a high-speed mixer and mixed, the temperature is raised to 70-100° C. within 5-20 minutes, the mixture is kept warm and stirred for 5-60 minutes, the mixture is discharged, and after cooling, the polycaprolactone-modified nano-calcium carbonate is obtained.
[0027] Preferably, the average particle size of nano calcium carbonate is 10 to 999 nm.
[0028] Preferably, the mass of polycaprolactone is 0.5-15wt% of the mass of nano-calcium carbonate.
[0029] Preferably, the rotation speed of the high-speed mixer is 500 to 10,000 rpm.
[0030] The second object of the present invention is achieved by the following technical solutions:
[0031] A method for preparing a highly dispersed flame retardant masterbatch comprises the following steps:
[0032] Weigh each component of the high-dispersion flame-retardant masterbatch, add it into a mixing tank at 100-180°C and mix it for 5-50 minutes, transfer it into a three-roll grinder for grinding and dispersion, and then press the ground and dispersed material through a double-roller machine, and cut it with a cutting machine to obtain a cake-shaped high-dispersion flame-retardant masterbatch.
[0033] Compared with the prior art, the present invention has the following beneficial effects:
[0034] 1. Flame retardant performance: This application adopts a composite flame retardant of antimony trioxide, borate, and organic phosphorus-nitrogen complex. The active substances produced by the organic phosphorus-nitrogen complex and borate after combustion and decomposition will have a synergistic effect with antimony trioxide, and form an effective flame retardant barrier in combination with the chlorine element in polyvinyl chloride. The composite flame retardant will produce a flame retardant effect greater than that of antimony trioxide alone;
[0035] Furthermore, when the organic phosphorus-nitrogen compound is a mixture of DOPO and MCA, the composite flame retardant of antimony trioxide, borate, DOPO, and MCA formed has better flame retardant properties than the composite flame retardant formed when the organic phosphorus-nitrogen compound is ammonium polyphosphate or melamine phosphate;
[0036] In addition, when the composite flame retardant further includes aluminum hydroxide and / or magnesium hydroxide, the synergistic effect of several materials enables the material to exhibit better flame retardant properties.
[0037] 2. Dispersibility: The present invention forms polycaprolactone on the surface of nano-calcium carbonate through a high temperature reaction of 70-100°C. The polycaprolactone melts into a liquid at high temperature and covers the surface of nano-calcium carbonate. The obtained PCL-modified nano-calcium carbonate can promote its uniform dispersion in the polymer and improve the dispersion effect of other components such as flame retardants in the polymer, ensuring the consistency and stability of product performance. And when other components such as flame retardants are added in the same amount, the addition of polycaprolactone-modified nano-calcium carbonate promotes the dispersion of flame retardants, which is more conducive to improving the flame retardant properties of plastic products.
[0038] 3. Thermal stability: The present invention mixes liquid calcium zinc stabilizer and powder calcium zinc stabilizer in a certain mass ratio, which has good light stability and thermal stability, can effectively prevent the material from aging due to light and high temperature, maintain the transparency and color brightness of the product, and improve the appearance quality and long-term performance of the product.
[0039] 4. Lubricity and processing performance: Metal soap lubricants combined with polyethylene wax as lubricants in the masterbatch of the present invention have better lubrication effects, reduce processing difficulty, and avoid undesirable phenomena.
[0040] In summary, the present invention not only significantly improves the flame retardant properties of the material, but also improves the stability and processing properties, reduces the processing difficulty and cost, and has broad application prospects by optimizing the flame retardant formula and improving the selection of dispersants, stabilizers and lubricants. DETAILED DESCRIPTION
[0041] Hereinafter, embodiments will be described in detail with respect to the high-dispersion flame-retardant masterbatch and the method for preparing the high-dispersion flame-retardant masterbatch of the present invention, however, these embodiments are exemplary and the present disclosure is not limited thereto.
[0042] High dispersion flame retardant masterbatch
[0043] The high-dispersion flame-retardant masterbatch provided by the present invention comprises the following components in parts by weight: 8 to 30 parts of high molecular polymer, 30 to 95 parts of composite flame retardant, 6 to 20 parts of plasticizer and 0.1 to 15 parts of auxiliary agent.
[0044] The composite flame retardant in the highly dispersed flame retardant masterbatch of the present invention:
[0045] The composite flame retardant of the present invention comprises antimony trioxide, borate, and an organic phosphorus-nitrogen complex, wherein the organic phosphorus-nitrogen complex is one or more of a mixture of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) and melamine cyanurate (MCA), melamine phosphate, and ammonium polyphosphate.
[0046] The active substances produced by organic phosphorus-nitrogen complexes and borates after combustion and decomposition will have a synergistic effect with antimony trioxide, and combine with the chlorine element in polyvinyl chloride to form an effective flame retardant barrier. Therefore, the use of a composite flame retardant composed of antimony trioxide, borate, and organic phosphorus-nitrogen complex will produce a flame retardant effect greater than that of using antimony trioxide alone.
[0047] In some embodiments of the present invention, the composite flame retardant comprises a mixture of antimony trioxide, borate, and organic phosphorus-nitrogen compound in a mass ratio of 1: (0.5-1.0): (0.5-1.0). Further preferably, the composite flame retardant comprises a mixture of antimony trioxide, borate, and organic phosphorus-nitrogen compound in a mass ratio of 1: (0.6-0.8): (0.6-0.8).
[0048] In some embodiments of the present invention, the organic phosphorus-nitrogen complex is further preferably a mixture of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and melamine cyanurate.
[0049] The inventors unexpectedly discovered that when the organic phosphorus-nitrogen complex is a mixture of DOPO and MCA, the composite flame retardant of antimony trioxide, borate, DOPO, and MCA formed has better flame retardant properties than the composite flame retardant formed when the organic phosphorus-nitrogen complex is ammonium polyphosphate or melamine phosphate.
[0050] In some embodiments of the present invention, the organic phosphorus-nitrogen complex is a mixture of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and melamine cyanurate in a mass ratio of (3-6): (2-4).
[0051] In some embodiments of the present invention, the composite flame retardant includes a mixture of antimony trioxide, borate, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and melamine cyanurate in a mass ratio of 1: (0.5-1.0): (0.3-0.6): (0.2-0.4).
[0052] In some embodiments of the present invention, the composite flame retardant preferably includes antimony trioxide, borate, organic phosphorus-nitrogen complex and metal hydroxide.
[0053] When the composite flame retardant further includes aluminum hydroxide and / or magnesium hydroxide, the synergistic effect of several materials enables the material to exhibit better flame retardant properties.
[0054] In some embodiments of the present invention, the composite flame retardant further preferably includes antimony trioxide, borate, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, melamine cyanurate and metal hydroxide.
[0055] In some embodiments of the present invention, the mass of the metal hydroxide is preferably 0.1-10wt% of the total mass of the composite flame retardant. Further preferably, the mass of the metal hydroxide is 1-8wt% of the total mass of the composite flame retardant, for example, 1, 2, 3, 4, 5, 6, 7 or 8wt%. Preferably, the metal hydroxide is aluminum hydroxide and / or magnesium hydroxide.
[0056] The borate in the composite flame retardant of the present invention is one or more of a metal salt of boric acid and a metal salt of fluoroboric acid. The metal here can be one or more of sodium, potassium, magnesium, barium, ammonium, calcium, manganese, nickel, copper, aluminum, zinc, cobalt, zirconium, etc.
[0057] The borate includes but is not limited to one or more of calcium borate, cobalt borate, anhydrous zinc borate, 3.5 hydrate zinc borate, sodium orthoborate, sodium perborate, sodium metaborate, sodium tetraborate, ammonium metaborate, ammonium pentaborate, calcium metaborate, barium metaborate, barium tetraborate, potassium metaborate, potassium tetraborate, potassium pentaborate, magnesium orthoborate, magnesium metaborate, trimagnesium tetraborate, pentamagnesium tetraborate, potassium tetrafluoroborate, sodium tetrafluoroborate, ammonium tetrafluoroborate, zinc tetrafluoroborate, calcium tetrafluoroborate, magnesium tetrafluoroborate, and barium metaborate.
[0058] The high molecular polymer in the highly dispersed flame retardant masterbatch of the present invention is:
[0059] The high molecular weight polymer in the highly dispersed flame retardant masterbatch needs to have good compatibility with the polymer product to be used. The specific type of high molecular weight polymer is selected according to the characteristics of the polymer product to be used. For example, it can be one or more of olefin polymers, ester polymers, ethylene polymers, styrene polymers, polyurethanes, etc.
[0060] Examples of the olefin-based polymer include polyethylene and polypropylene.
[0061] Examples of the ester polymer include polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polytrimethylene terephthalate (PTT), and polyethylene naphthalate (PEN).
[0062] Examples of the vinyl polymer include polyvinyl chloride, polyvinylidene chloride, polyvinyl alcohol, ethylene-vinyl acetate copolymer, and chloroacetate resin.
[0063] Examples of the styrene-based polymer include polystyrene, styrene-acrylonitrile resin, and styrene-butadiene-acrylonitrile resin.
[0064] In some embodiments of the present invention, the high molecular polymer is one or more of polyvinyl chloride, polyethylene, polypropylene, polyurethane, polyester, polyvinyl alcohol, chloroacetic acid resin, and ethylene-vinyl acetate copolymer.
[0065] In some embodiments of the present invention, the high molecular polymer is further preferably one or more of polyvinyl chloride, chloroacetic acid resin, and ethylene-vinyl acetate copolymer.
[0066] Plasticizer in the highly dispersed flame retardant masterbatch of the present invention:
[0067] In some embodiments of the present invention, the plasticizer is one or more of pyromellitic acid ester plasticizers, trimellitic acid ester plasticizers, phthalic acid ester plasticizers, terephthalic acid ester plasticizers, phosphate ester plasticizers, and epoxidized vegetable oil.
[0068] The pyromellitic acid ester plasticizer can be listed as one or more of tetra-n-hexyl pyromellitic acid, tetra-n-heptyl pyromellitic acid, tetra-n-octyl pyromellitic acid, tetra(2-ethylhexyl)pyromellitic acid, tetra-n-nonyl pyromellitic acid, tetra-n-decyl pyromellitic acid, tetra-isodecyl pyromellitic acid, tetra-n-undecyl pyromellitic acid, tetra-n-dodecyl pyromellitic acid, and the like.
[0069] The trimellitic acid ester plasticizer includes one or more of trioctyl trimellitic acid, triglycerol trimellitic acid, and the like.
[0070] The phthalate plasticizer includes one or more of diheptyl phthalate, dioctyl phthalate, dinonyl phthalate, diisodecyl phthalate, diundecyl phthalate, didecyl phthalate, tridecyl phthalate, di(2-ethylhexyl) phthalate, dicyclohexyl phthalate, dibenzyl phthalate, halogenated dialkyl phthalates, and the like.
[0071] The terephthalate plasticizer includes one or more of dioctyl terephthalate (DOTP), diisononyl terephthalate, diisodecyl terephthalate, di(2-ethylhexyl) terephthalate, and the like.
[0072] The phosphate plasticizer includes one or more of tri(isopropylphenyl)phosphate, tri(2-chloroethyl)phosphate, bisphenol A-bis(diphenyl phosphate) (BDP), tri(2-chloroethyl)phosphate (TCEP), tri(butoxyethyl)phosphate, etc.
[0073] Examples of the epoxidized vegetable oil include epoxidized soybean oil and epoxidized linseed oil.
[0074] Further preferably, the plasticizer is one or more of dioctyl phthalate, dinonyl phthalate, diisodecyl phthalate, diundecyl phthalate, didodecyl phthalate, tridecyl phthalate, dioctyl terephthalate (DOTP), tri(isopropylphenyl) phosphate, dialkyl tetrahalophthalate, tri(2-chloroethyl) phosphate (TCEP), bisphenol A-bis(diphenyl phosphate) (BDP), and epoxidized soybean oil.
[0075] The additives in the highly dispersed flame retardant masterbatch of the present invention are:
[0076] In some embodiments of the present invention, the auxiliary agent includes one or more of a dispersant, a stabilizer, and a lubricant.
[0077] The dispersant of the present invention is preferably polycaprolactone (PCL) modified nano calcium carbonate.
[0078] In some embodiments of the present invention, the preparation method of the polycaprolactone modified nano calcium carbonate comprises the following steps:
[0079] The nano-calcium carbonate and polycaprolactone are put into a high-speed mixer and mixed, the temperature is raised to 70-100° C. within 5-20 minutes, the mixture is kept warm and stirred for 5-60 minutes, the mixture is discharged, and after cooling, the polycaprolactone-modified nano-calcium carbonate is obtained.
[0080] In the preparation method of polycaprolactone modified nano-calcium carbonate, preferably, the average particle size of the nano-calcium carbonate is 10-999nm. Preferably, the mass of polycaprolactone is 0.5-15wt% of the mass of the nano-calcium carbonate, more preferably 1-10wt%, for example, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10wt%. Preferably, the speed of the high-speed mixer is 500-10000 rpm.
[0081] Nano calcium carbonate is used as a functional component in the masterbatch of the present invention, which can not only improve the mechanical properties and processing properties of polymer products, but also can be used as a dispersant to improve the dispersing effect of other components. Polycaprolactone is formed on the surface of nano calcium carbonate through a high temperature reaction of 70 to 100°C. Polycaprolactone melts into a liquid at high temperature and covers the surface of nano calcium carbonate, reducing the molecular force between nano calcium carbonate powders, promoting its uniform dispersion in high molecular polymers, and improving the dispersing effect of other components such as flame retardants in high molecular polymers, ensuring the consistency and stability of product performance. And when other components such as flame retardants are added in equal amounts, the addition of polycaprolactone-modified nano calcium carbonate promotes the dispersion of flame retardants, which is more conducive to improving the flame retardant properties of plastic products.
[0082] The stabilizer of the present invention is preferably a liquid calcium zinc stabilizer or a powdery calcium zinc stabilizer.
[0083] More preferably, the stabilizer is a mixture of a liquid calcium zinc stabilizer and a powdery calcium zinc stabilizer in a mass ratio of 1:0.3 to 0.6.
[0084] Calcium zinc stabilizer has a better light stabilization effect, which can not only prevent the material from aging due to light, but also maintain the transparency and color brightness of the product, and improve the appearance quality of the product; it also has a better thermal stabilization effect, which can effectively prevent the material from decomposing at high temperature and ensure the long-term use performance of the product. Calcium zinc stabilizer is mainly divided into two forms: liquid and powder. Liquid calcium zinc stabilizer has good compatibility with polymers, is easy to mix, and is easy to process; powder calcium zinc stabilizer has good stability, is suitable for high temperature processing conditions, and provides better stabilization effect. In the production process, a single liquid or powder calcium zinc stabilizer is generally selected for application according to actual needs, and the present invention mixes the liquid calcium zinc stabilizer and the powder calcium zinc stabilizer in a certain mass ratio, and it is found that the mixture has a better stabilization effect than a single liquid or powder calcium zinc stabilizer.
[0085] The lubricant of the present invention includes one or more of metal soap lubricants, hydrocarbon lubricants, fatty acid lubricants, and fatty acid ester lubricants.
[0086] Examples of the metal soap lubricant include one or more of zinc stearate, calcium stearate, magnesium stearate, aluminum stearate, and lead stearate.
[0087] The hydrocarbon lubricant may be one or more of paraffin wax, natural paraffin wax, microcrystalline paraffin wax, polyethylene wax, halogenated hydrocarbons, and the like.
[0088] Examples of the fatty acid lubricant include one or more of stearic acid, palmitic acid, oleic acid, linoleic acid, and myristic acid.
[0089] Examples of the fatty acid ester lubricant include one or more of stearic acid ester, palmitic acid ester, oleic acid ester, linoleic acid ester, and myristic acid ester.
[0090] Preferably, the lubricant is a metal soap lubricant and a polyethylene wax.
[0091] More preferably, the lubricant is a mixture of a metal soap lubricant and polyethylene wax in a mass ratio of 1:0.1 to 0.5.
[0092] Metal soap lubricants such as zinc stearate and calcium stearate are combined with polyethylene wax (i.e., low molecular weight polyethylene with a molecular weight between 1000 and 5000) as lubricants in the masterbatch of the present invention, which has a better lubricating effect, is beneficial to weaken the cohesive force between polymer molecules, reduce internal friction, reduce melt viscosity, and increase melt fluidity. The improvement of fluidity can ensure the smoothness of the product surface, reduce bubbles, and reduce defects such as weld lines.
[0093] In some embodiments of the present invention, the auxiliary agent includes a dispersant, a stabilizer, and a lubricant; in the highly dispersed flame retardant masterbatch, the dispersant is 0.1 to 4 parts, the stabilizer is 0.5 to 6.0 parts, and the lubricant is 0.1 to 3 parts.
[0094] In some embodiments of the present invention, the auxiliary agent also includes a series of substances that can improve or impart specific properties to the polymer, such as colorants and antistatic agents.
[0095] Preparation method of high-dispersion flame-retardant masterbatch
[0096] The method for preparing a highly dispersed flame retardant masterbatch provided by the present invention comprises the following steps:
[0097] Weigh each component of the high-dispersion flame-retardant masterbatch, add it into a mixing tank at 100-180°C and mix it for 5-50 minutes, transfer it into a three-roll grinder for grinding and dispersion, and then press the ground and dispersed material through a double-roller machine, and cut it with a cutting machine to obtain a cake-shaped high-dispersion flame-retardant masterbatch.
[0098] Preferably, during the grinding and dispersing process, the grinding is performed 2 to 4 times, each time for 10 to 30 minutes.
[0099] Preferably, the roller temperature of the double-roll mill is 80-120°C.
[0100] The technical scheme of the present invention is further described below by specific embodiments. It should be understood that the specific embodiments described herein are only used to help understand the present invention and are not intended to be used for specific limitations of the present invention. Unless otherwise specified, the raw materials used in the embodiments of the present invention are all commonly used raw materials in the art, and the methods used in the embodiments are all conventional methods in the art.
[0101] The following are the sources of raw materials in the embodiments and comparative examples:
[0102] Polyvinyl chloride: purchased from Tianjin Bohai Chemical Development Co., Ltd., DG-700. Chlorovinyl resin is CP-430 of Hanwha. 3.5-hydrated zinc borate: purchased from Shandong Bio Industrial Co., Ltd. Melamine phosphate: purchased from Budenheim, Budit 3141. Ammonium polyphosphate: purchased from Shandong Taixing New Materials Co., Ltd., HT-208. Melamine cyanurate (MCA): purchased from Melapur MC25 produced by BASF. Nano calcium carbonate: average particle size is 30nm, purchased from Shandong Haize Nano Materials Co., Ltd. Polycaprolactone (PCL): purchased from Shenzhen Guanghua Weiye Co., Ltd., Esun 500C. Liquid calcium zinc stabilizer: purchased from Zhejiang Jiaao Environmental Protection Technology Co., Ltd., JCZ-100. Powder calcium zinc stabilizer: purchased from Zhejiang Jiaao Environmental Protection Technology Co., Ltd., JCZ-6503B. .
[0103] Example 1
[0104] The highly dispersed flame retardant masterbatch provided in this embodiment includes the following components in parts by weight:
[0105] Polyvinyl chloride: 6 parts; composite flame retardant: 80 parts, epoxy soybean oil: 5 parts, BDP: 5 parts, liquid calcium zinc stabilizer: 1.0 parts, powdered calcium zinc stabilizer: 0.5 parts, zinc stearate: 1 part, polyethylene wax: 0.4 parts, polycaprolactone modified nano calcium carbonate: 2 parts. Among them, the composite flame retardant is a mixture of antimony trioxide, 3.5-water zinc borate, and melamine phosphate, and the parts of antimony trioxide, 3.5-water zinc borate, and melamine phosphate are 34 parts, 23 parts, and 23 parts respectively.
[0106] The preparation method of polycaprolactone modified nano calcium carbonate comprises the following steps:
[0107] 93 parts of nano-calcium carbonate and 7 parts of polycaprolactone were put into a 3000 rpm high-speed mixer for mixing, the temperature was raised to 80° C. within 10 minutes, the mixture was kept warm and stirred for 30 minutes, the mixture was discharged, and after cooling, polycaprolactone-modified nano-calcium carbonate was obtained.
[0108] This embodiment also provides a method for preparing a highly dispersed flame retardant masterbatch, comprising the following steps:
[0109] Weigh the components of the highly dispersed flame retardant masterbatch according to the above weight proportions, add them into a mixing cylinder at 150°C and mix for 30 minutes, move them into a three-roll grinder for grinding and dispersion, grind them 3 times, each time for 20 minutes, and then press the ground and dispersed materials through a double-roll mill (roller temperature is 100°C) to form them, and cut them with a cutting machine to obtain a cake-shaped highly dispersed flame retardant masterbatch.
[0110] Example 2
[0111] The highly dispersed flame retardant masterbatch provided in this embodiment includes the following components in parts by weight:
[0112] Polyvinyl chloride: 6 parts; composite flame retardant: 80 parts, epoxy soybean oil: 5 parts, BDP: 5 parts, liquid calcium zinc stabilizer: 1.0 parts, powdered calcium zinc stabilizer: 0.5 parts, zinc stearate: 1 part, polyethylene wax: 0.4 parts, polycaprolactone modified nano calcium carbonate: 2 parts. Among them, the composite flame retardant is a mixture of antimony trioxide, 3.5-water zinc borate, and ammonium polyphosphate, and the parts of antimony trioxide, 3.5-water zinc borate, and ammonium polyphosphate are 34 parts, 23 parts, and 23 parts respectively.
[0113] The preparation method of polycaprolactone-modified nano-calcium carbonate and the preparation method of highly dispersed flame retardant masterbatch are the same as those in Example 1.
[0114] Example 3
[0115] The highly dispersed flame retardant masterbatch provided in this embodiment includes the following components in parts by weight:
[0116] Polyvinyl chloride: 6 parts; composite flame retardant: 80 parts, epoxy soybean oil: 5 parts, BDP: 5 parts, liquid calcium zinc stabilizer: 1.0 parts, powdered calcium zinc stabilizer: 0.5 parts, zinc stearate: 1 part, polyethylene wax: 0.4 parts, polycaprolactone modified nano calcium carbonate: 2 parts. Among them, the composite flame retardant is a mixture of antimony trioxide, 3.5-water zinc borate, DOPO, and MCA, and the parts of antimony trioxide, 3.5-water zinc borate, DOPO, and MCA are 34 parts, 23 parts, 13 parts, and 10 parts respectively.
[0117] The preparation method of polycaprolactone-modified nano-calcium carbonate and the preparation method of highly dispersed flame retardant masterbatch are the same as those in Example 1.
[0118] Example 4
[0119] The highly dispersed flame retardant masterbatch provided in this embodiment includes the following components in parts by weight:
[0120] Polyvinyl chloride: 6 parts; composite flame retardant: 80 parts, epoxidized soybean oil: 5 parts, BDP: 5 parts, liquid calcium zinc stabilizer: 1.0 parts, powdered calcium zinc stabilizer: 0.5 parts, zinc stearate: 1 part, polyethylene wax: 0.4 parts, polycaprolactone modified nano calcium carbonate: 2 parts. Among them, the composite flame retardant is a mixture of antimony trioxide, 3.5-water zinc borate, DOPO, and MCA, and the parts of antimony trioxide, 3.5-water zinc borate, DOPO, and MCA are 30 parts, 22 parts, 18 parts, and 10 parts respectively.
[0121] The preparation method of polycaprolactone-modified nano-calcium carbonate and the preparation method of highly dispersed flame retardant masterbatch are the same as those in Example 1.
[0122] Example 5
[0123] The highly dispersed flame retardant masterbatch provided in this embodiment includes the following components in parts by weight:
[0124] Polyvinyl chloride: 6 parts; composite flame retardant: 80 parts, epoxidized soybean oil: 5 parts, BDP: 5 parts, liquid calcium zinc stabilizer: 1.0 parts, powdered calcium zinc stabilizer: 0.5 parts, zinc stearate: 1 part, polyethylene wax: 0.4 parts, polycaprolactone modified nano calcium carbonate: 2 parts. Among them, the composite flame retardant is a mixture of antimony trioxide, 3.5-water zinc borate, DOPO, MCA, and aluminum hydroxide, and the parts of antimony trioxide, 3.5-water zinc borate, DOPO, MCA, and aluminum hydroxide are 33 parts, 22 parts, 12 parts, 9 parts, and 4 parts respectively.
[0125] The preparation method of polycaprolactone-modified nano-calcium carbonate and the preparation method of highly dispersed flame retardant masterbatch are the same as those in Example 1.
[0126] Example 6
[0127] The highly dispersed flame retardant masterbatch provided in this embodiment includes the following components in parts by weight:
[0128] Polyvinyl chloride: 6 parts; composite flame retardant: 80 parts, epoxy soybean oil: 5 parts, BDP: 5 parts, liquid calcium zinc stabilizer: 1.0 parts, powdered calcium zinc stabilizer: 0.5 parts, zinc stearate: 1 part, polyethylene wax: 0.4 parts, polycaprolactone modified nano calcium carbonate: 2 parts. Among them, the composite flame retardant is a mixture of antimony trioxide, 3.5-water zinc borate, DOPO, MCA, and magnesium hydroxide, and the parts of antimony trioxide, 3.5-water zinc borate, DOPO, MCA, and magnesium hydroxide are 29 parts, 21 parts, 17 parts, 9 parts, and 4 parts respectively.
[0129] The preparation method of polycaprolactone-modified nano-calcium carbonate and the preparation method of highly dispersed flame retardant masterbatch are the same as those in Example 1.
[0130] Example 7
[0131] The highly dispersed flame retardant masterbatch provided in this embodiment includes the following components in parts by weight:
[0132] Polyvinyl chloride: 6 parts; composite flame retardant: 80 parts, epoxidized soybean oil: 5 parts, BDP: 5 parts, liquid calcium zinc stabilizer: 1.0 parts, powdered calcium zinc stabilizer: 0.5 parts, zinc stearate: 1 part, polyethylene wax: 0.4 parts, nano calcium carbonate: 2 parts. Among them, the composite flame retardant is a mixture of antimony trioxide, 3.5-water zinc borate, DOPO, and MCA, and the parts of antimony trioxide, 3.5-water zinc borate, DOPO, and MCA are 34 parts, 23 parts, 13 parts, and 10 parts respectively.
[0133] The preparation method of the highly dispersed flame retardant masterbatch is the same as that in Example 1.
[0134] Example 8
[0135] The highly dispersed flame retardant masterbatch provided in this embodiment includes the following components in parts by weight:
[0136] Polyvinyl chloride: 6 parts; composite flame retardant: 80 parts, epoxy soybean oil: 5 parts, BDP: 5 parts, liquid calcium zinc stabilizer: 1.0 parts, powdered calcium zinc stabilizer: 0.5 parts, zinc stearate: 1 part, polyethylene wax: 0.4 parts, polycaprolactone: 0.14 parts, nano calcium carbonate: 1.86 parts. Among them, the composite flame retardant is a mixture of antimony trioxide, 3.5-water zinc borate, DOPO, and MCA, and the parts of antimony trioxide, 3.5-water zinc borate, DOPO, and MCA are 34 parts, 23 parts, 13 parts, and 10 parts respectively.
[0137] The method for preparing a highly dispersed flame retardant masterbatch provided in this embodiment comprises the following steps:
[0138] According to the above weight proportions, polyvinyl chloride, composite flame retardant, epoxy soybean oil, BDP, liquid calcium zinc stabilizer, powdered calcium zinc stabilizer, zinc stearate, polyethylene wax, polycaprolactone and nano calcium carbonate were weighed, added into a mixing cylinder at 150°C and mixed for 30 minutes, transferred into a three-roll grinder for grinding and dispersion, ground 3 times, each time for 20 minutes, and then the ground and dispersed materials were pressed into shape by a double-roll mill (roller temperature was 100°C), and cut by a cutting machine to obtain a cake-shaped highly dispersed flame retardant masterbatch.
[0139] Example 9
[0140] The highly dispersed flame retardant masterbatch provided in this embodiment includes the following components in parts by weight:
[0141] Polyvinyl chloride: 6 parts; composite flame retardant: 80 parts, epoxidized soybean oil: 5 parts, BDP: 5 parts, liquid calcium zinc stabilizer: 1.5 parts, zinc stearate: 1 part, polyethylene wax: 0.4 parts, polycaprolactone modified nano calcium carbonate: 2 parts. Among them, the composite flame retardant is a mixture of antimony trioxide, 3.5-water zinc borate, DOPO, and MCA, and the parts of antimony trioxide, 3.5-water zinc borate, DOPO, and MCA are 34 parts, 23 parts, 13 parts, and 10 parts respectively.
[0142] The preparation method of polycaprolactone-modified nano-calcium carbonate and the preparation method of highly dispersed flame retardant masterbatch are the same as those in Example 1.
[0143] Example 10
[0144] The highly dispersed flame retardant masterbatch provided in this embodiment includes the following components in parts by weight:
[0145] Polyvinyl chloride: 6 parts; composite flame retardant: 80 parts, epoxy soybean oil: 5 parts, BDP: 5 parts, powdered calcium zinc stabilizer: 1.5 parts, zinc stearate: 1 part, polyethylene wax: 0.4 parts, polycaprolactone modified nano calcium carbonate: 2 parts. Among them, the composite flame retardant is a mixture of antimony trioxide, 3.5-water zinc borate, DOPO, and MCA, and the parts of antimony trioxide, 3.5-water zinc borate, DOPO, and MCA are 34 parts, 23 parts, 13 parts, and 10 parts respectively.
[0146] The preparation method of polycaprolactone-modified nano-calcium carbonate and the preparation method of highly dispersed flame retardant masterbatch are the same as those in Example 1.
[0147] Embodiment 11
[0148] The highly dispersed flame retardant masterbatch provided in this embodiment includes the following components in parts by weight:
[0149] Polyvinyl chloride: 6 parts; composite flame retardant: 80 parts, epoxy soybean oil: 5 parts, BDP: 5 parts, liquid calcium zinc stabilizer: 0.5 parts, powdered calcium zinc stabilizer: 1 part, zinc stearate: 1 part, polyethylene wax: 0.4 parts, polycaprolactone modified nano calcium carbonate: 2 parts. Among them, the composite flame retardant is a mixture of antimony trioxide, 3.5-water zinc borate, DOPO, and MCA, and the parts of antimony trioxide, 3.5-water zinc borate, DOPO, and MCA are 34 parts, 23 parts, 13 parts, and 10 parts respectively.
[0150] The preparation method of polycaprolactone-modified nano-calcium carbonate and the preparation method of highly dispersed flame retardant masterbatch are the same as those in Example 1.
[0151] Example 12
[0152] The highly dispersed flame retardant masterbatch provided in this embodiment includes the following components in parts by weight:
[0153] Polyvinyl chloride: 6 parts; composite flame retardant: 80 parts, epoxy soybean oil: 5 parts, BDP: 5 parts, liquid calcium zinc stabilizer: 1.0 parts, powdered calcium zinc stabilizer: 0.5 parts, zinc stearate: 1.4 parts, polycaprolactone modified nano calcium carbonate: 2 parts. Among them, the composite flame retardant is a mixture of antimony trioxide, 3.5-water zinc borate, DOPO, and MCA, and the parts of antimony trioxide, 3.5-water zinc borate, DOPO, and MCA are 34 parts, 23 parts, 13 parts, and 10 parts respectively.
[0154] The preparation method of polycaprolactone-modified nano-calcium carbonate and the preparation method of highly dispersed flame retardant masterbatch are the same as those in Example 1.
[0155] Example 13
[0156] The highly dispersed flame retardant masterbatch provided in this embodiment includes the following components in parts by weight:
[0157] Polyvinyl chloride: 6 parts; composite flame retardant: 80 parts, epoxidized soybean oil: 5 parts, BDP: 5 parts, liquid calcium zinc stabilizer: 1.0 parts, powdered calcium zinc stabilizer: 0.5 parts, polyethylene wax: 1.4 parts, polycaprolactone modified nano calcium carbonate: 2 parts. Among them, the composite flame retardant is a mixture of antimony trioxide, 3.5-water zinc borate, DOPO, and MCA, and the parts of antimony trioxide, 3.5-water zinc borate, DOPO, and MCA are 34 parts, 23 parts, 13 parts, and 10 parts respectively.
[0158] The preparation method of polycaprolactone-modified nano-calcium carbonate and the preparation method of highly dispersed flame retardant masterbatch are the same as those in Example 1.
[0159] Embodiment 14
[0160] The highly dispersed flame retardant masterbatch provided in this embodiment includes the following components in parts by weight:
[0161] Polyvinyl chloride: 6 parts; composite flame retardant: 80 parts, epoxidized soybean oil: 5 parts, BDP: 5 parts, liquid calcium zinc stabilizer: 1.0 parts, powdered calcium zinc stabilizer: 0.5 parts, zinc stearate: 0.7 parts, polyethylene wax: 0.7 parts, polycaprolactone modified nano calcium carbonate: 2 parts. Among them, the composite flame retardant is a mixture of antimony trioxide, 3.5-water zinc borate, DOPO, and MCA, and the parts of antimony trioxide, 3.5-water zinc borate, DOPO, and MCA are 34 parts, 23 parts, 13 parts, and 10 parts respectively.
[0162] The preparation method of polycaprolactone-modified nano-calcium carbonate and the preparation method of highly dispersed flame retardant masterbatch are the same as those in Example 1.
[0163] Embodiment 15
[0164] The highly dispersed flame retardant masterbatch provided in this embodiment includes the following components in parts by weight:
[0165] Polyvinyl chloride: 4 parts, chloroacetic acid resin: 1 part, composite flame retardant: 85 parts, epoxidized soybean oil: 5 parts, TCEP: 7 parts, liquid calcium zinc stabilizer: 0.5 parts, powdered calcium zinc stabilizer: 0.3 parts, zinc stearate: 0.5 parts, polyethylene wax: 0.2 parts, polycaprolactone modified nano calcium carbonate: 1.5 parts.
[0166] The composite flame retardant is a mixture of antimony trioxide, 3.5% zinc borate, DOPO and MCA, and the proportions of antimony trioxide, 3.5% zinc borate, DOPO and MCA are 36 parts, 28 parts, 11 parts and 10 parts respectively.
[0167] The preparation method of polycaprolactone modified nano calcium carbonate comprises the following steps:
[0168] 90 parts of nano-calcium carbonate and 10 parts of polycaprolactone were put into a 5000 rpm high-speed mixer for mixing, the temperature was raised to 85° C. within 15 minutes, the mixture was kept warm and stirred for 20 minutes, the mixture was discharged, and after cooling, polycaprolactone-modified nano-calcium carbonate was obtained.
[0169] This embodiment also provides a method for preparing a highly dispersed flame retardant masterbatch, comprising the following steps:
[0170] Weigh the components of the highly dispersed flame retardant masterbatch according to the above weight proportions, add them into a mixing cylinder at 160°C and mix for 25 minutes, move them into a three-roll grinder for grinding and dispersion, grind 4 times, each time for 15 minutes, and then press the ground and dispersed materials through a double-roll mill (roller temperature is 110°C) to form, and cut them with a cutting machine to obtain a cake-shaped highly dispersed flame retardant masterbatch.
[0171] Comparative Example 1
[0172] The difference between Comparative Example 1 and Example 3 is that the flame retardant in Comparative Example 1 is antimony trioxide.
[0173] That is, the highly dispersed flame retardant masterbatch provided in the comparative example comprises the following components in parts by weight:
[0174] Polyvinyl chloride: 6 parts; antimony trioxide: 80 parts, epoxidized soybean oil: 5 parts, BDP: 5 parts, liquid calcium zinc stabilizer: 1.0 parts, powdered calcium zinc stabilizer: 0.5 parts, zinc stearate: 1 part, polyethylene wax: 0.4 parts, polycaprolactone modified nano calcium carbonate: 2 parts.
[0175] The preparation method of polycaprolactone-modified nano-calcium carbonate and the preparation method of highly dispersed flame retardant masterbatch are the same as those in Example 3.
[0176] Comparative Example 2
[0177] The difference between Comparative Example 2 and Example 3 is that the flame retardant in Comparative Example 2 is 3.5-hydrate zinc borate.
[0178] That is, the highly dispersed flame retardant masterbatch provided in the comparative example comprises the following components in parts by weight:
[0179] Polyvinyl chloride: 6 parts, 3.5 parts of zinc borate with water: 80 parts, epoxidized soybean oil: 5 parts, BDP: 5 parts, liquid calcium zinc stabilizer: 1.0 parts, powdered calcium zinc stabilizer: 0.5 parts, zinc stearate: 1 parts, polyethylene wax: 0.4 parts, polycaprolactone modified nano calcium carbonate: 2 parts.
[0180] The preparation method of polycaprolactone-modified nano-calcium carbonate and the preparation method of highly dispersed flame retardant masterbatch are the same as those in Example 3.
[0181] Comparative Example 3
[0182] The difference between Comparative Example 3 and Example 3 is that the flame retardant in Comparative Example 3 is antimony trioxide and 3.5-hydrate zinc borate.
[0183] That is, the highly dispersed flame retardant masterbatch provided in the comparative example comprises the following components in parts by weight:
[0184] Polyvinyl chloride: 6 parts, antimony trioxide: 57 parts, 3.5-water zinc borate: 23 parts, epoxidized soybean oil: 5 parts, BDP: 5 parts, liquid calcium zinc stabilizer: 1.0 parts, powdered calcium zinc stabilizer: 0.5 parts, zinc stearate: 1 part, polyethylene wax: 0.4 parts, polycaprolactone modified nano calcium carbonate: 2 parts.
[0185] The preparation method of polycaprolactone-modified nano-calcium carbonate and the preparation method of highly dispersed flame retardant masterbatch are the same as those in Example 3.
[0186] Comparative Example 4
[0187] The difference between Comparative Example 4 and Example 3 is that the flame retardant in Comparative Example 4 is antimony trioxide, 3.5-hydrate zinc borate and DOPO.
[0188] That is, the highly dispersed flame retardant masterbatch provided in the comparative example comprises the following components in parts by weight:
[0189] Polyvinyl chloride: 6 parts, antimony trioxide: 34 parts, 3.5-water zinc borate: 23 parts, DOPO: 23 parts, epoxidized soybean oil: 5 parts, BDP: 5 parts, liquid calcium zinc stabilizer: 1.0 parts, powdered calcium zinc stabilizer: 0.5 parts, zinc stearate: 1 part, polyethylene wax: 0.4 parts, polycaprolactone modified nano calcium carbonate: 2 parts.
[0190] The preparation method of polycaprolactone-modified nano-calcium carbonate and the preparation method of highly dispersed flame retardant masterbatch are the same as those in Example 3.
[0191] Comparative Example 5
[0192] The difference between Comparative Example 5 and Example 3 is that the flame retardant in Comparative Example 5 is antimony trioxide, 3.5-hydrate zinc borate and MCA.
[0193] That is, the highly dispersed flame retardant masterbatch provided in the comparative example comprises the following components in parts by weight:
[0194] Polyvinyl chloride: 6 parts, antimony trioxide: 34 parts, 3.5-water zinc borate: 23 parts, MCA: 23 parts, epoxidized soybean oil: 5 parts, BDP: 5 parts, liquid calcium zinc stabilizer: 1.0 parts, powdered calcium zinc stabilizer: 0.5 parts, zinc stearate: 1 part, polyethylene wax: 0.4 parts, polycaprolactone modified nano calcium carbonate: 2 parts.
[0195] The preparation method of polycaprolactone-modified nano-calcium carbonate and the preparation method of highly dispersed flame retardant masterbatch are the same as those in Example 3.
[0196] Table 1 Flame retardant masterbatch of the embodiment and comparative example includes the following components in parts by weight:
[0197]
[0198]
[0199] Performance Testing
[0200] 1. Flame retardancy:
[0201] (1) UL94 vertical burning test:
[0202] Experiment in Group A: 8 g of the flame retardant masterbatch of each embodiment and comparative example was injection molded with 180 g of polyvinyl chloride masterbatch to obtain a sample with a size of 125 mm × 13 mm × 4 mm. A vertical combustion test was carried out in accordance with the UL94 standard. The combustion levels were divided into V0, V1, V2, and no level.
[0203] Experiment in Group B: 5 g of the flame retardant masterbatch of each embodiment and comparative example was injection molded with 180 g of polyvinyl chloride masterbatch to obtain a sample with a size of 125 mm × 13 mm × 4 mm. A vertical combustion test was carried out in accordance with the UL94 standard. The combustion levels are divided into V0, V1, V2, and no level.
[0204] (2) Limiting oxygen index test (LOI): 8 g of the flame retardant masterbatch of each embodiment and comparative example was injection molded with 180 g of polyvinyl chloride masterbatch to obtain a sample with a size of 120 mm×10 mm×4 mm. The sample was measured according to ASTM D2863 standard to obtain the minimum oxygen concentration expressed in volume percentage that can just maintain the combustion of the material in an oxygen-nitrogen mixed gas flow.
[0205] The results are shown in Table 4.
[0206] 2. Heat resistance: 8 g of the flame retardant masterbatch of Examples 3, 9-11 and 100 g of polyvinyl chloride masterbatch were injection molded to obtain a test piece with a size of 150 mm × 150 mm × 2 mm. The test piece was cut into two pieces, one of which was used as a comparative reference sample and stored at room temperature, and the other was subjected to a heat resistance test at 200 ± 2 ° C (20 min). The color difference between the test sample and the comparative reference sample stored in the dark is represented by ΔE:
[0207]
[0208] Among them, ΔL represents the brightness difference, Δa represents the red-green difference, and Δb represents the yellow-blue difference.
[0209] The smaller the ΔE value, the closer the colors of the two are, indicating better heat resistance. The results are shown in Table 2.
[0210] 3. Migration resistance: 8g of the flame retardant masterbatch of each embodiment and comparative example and 180g of polyvinyl chloride masterbatch were injection molded, and a 5cm×5cm film was cut from each, and placed between two 7cm×7cm black polyvinyl chloride soft films. A smooth-surfaced pressure roller was used to squeeze out the air between the black polyvinyl chloride soft film and the experimental sample to ensure that they fit tightly. Pressurize with 5kg and put it in an 80℃ oven for 24 hours. Take out the test combination, separate the black polyvinyl chloride soft film from the experimental sample, and cool it to room temperature. Take the black area (edge part) of the black polyvinyl chloride soft film that is not bonded to the experimental sample as the reference benchmark, and visually compare it with the stained area of the black polyvinyl chloride soft film in the bonded part to determine the migration level of the masterbatch. Level 5 means no migration, and level 1 means severe migration.
[0211] The results are shown in Table 4.
[0212] 4. Lubricity: 8g of the flame retardant masterbatch of Examples 3, 12-14 and 100g of polyvinyl chloride masterbatch were injection molded, and then the melt flow rate (MFR value) of the sample was tested using a melt flow rate meter at 190°C and a 5KG weight. The larger the MFR value, the better the lubrication effect. The results are shown in Table 3.
[0213] Table 2 Heat resistance of flame retardant masterbatch of Examples 3, 9-11
[0214] Example ΔE Example 3 0.52 Example 9 0.72 Example 10 0.68 Embodiment 11 0.63
[0215] As can be seen from Table 2, the ΔE of Example 9 using a liquid calcium zinc stabilizer after high temperature treatment is 0.72, while the ΔE of Example 10 using a powdered calcium zinc stabilizer after high temperature treatment is as high as 0.68. Mixing the liquid calcium zinc stabilizer and the powdered calcium zinc stabilizer is beneficial to improving the heat resistance of the material, so the ΔE of Examples 3 and 11 is reduced relative to that of Examples 9 and 10. In particular, Example 3 has the lowest ΔE, indicating that the calcium zinc stabilizer mixture used in Example 3 has better thermal stability.
[0216] Table 3 MFR values of flame retardant masterbatches of Examples 3, 12-14
[0217] Example MFR value (g / 10min) Example 3 5.1 Example 12 4.5 Example 13 4.4 Embodiment 14 4.9
[0218] As can be seen from Table 3, Example 12 uses a single zinc stearate as a lubricant, and Example 13 uses a single polyethylene wax as a lubricant, and the MFR value of the polymer is relatively low. Mixing zinc stearate and polyethylene wax as a lubricant is beneficial to improving the lubrication effect, which is manifested in an increase in the MFR value of the polymer, as shown in Examples 3 and 14. In particular, Example 3, which uses a more suitable mass ratio of zinc stearate and polyethylene wax, has a better lubrication effect.
[0219] Table 4 Flame retardant properties and migration resistance of the embodiments and comparative examples
[0220]
[0221]
[0222] In the UL94 test of Group A, due to the relatively high content of flame retardant in the samples, the flame retardant levels of the samples of Examples 1-15 can all reach V0, while the samples of Comparative Examples 1-5 can only reach V1. The content of flame retardant in the samples of Group B is reduced, and the flame retardant levels of the samples of Examples 3-6, 9-15 can still reach V0, while the flame retardant levels of the samples of Examples 1-2, 7-8 and Comparative Examples 3-5 are V1, and the level of the sample of Comparative Example 1-2 can only reach V2. The above experimental results show that when the flame retardant is antimony trioxide, 3.5 zinc borate water, or an organic phosphorus-nitrogen complex, its flame retardant performance is better than antimony trioxide, 3.5 zinc borate water, or a mixture of the two, and is also better than a mixed flame retardant formed by antimony trioxide, 3.5 zinc borate water, and DOPO or MCA. Furthermore, when the organic phosphorus-nitrogen compound is a mixture of DOPO and MCA, the composite flame retardant of antimony trioxide, 3.5-hydrate zinc borate, DOPO, and MCA has better flame retardant properties than the composite flame retardant formed by the organic phosphorus-nitrogen compound being ammonium polyphosphate or melamine phosphate. In addition, when the composite flame retardant further includes aluminum hydroxide and / or magnesium hydroxide, the material exhibits better flame retardant properties.
[0223] Regarding the influence of the dispersant, the dispersant of Example 7 is unmodified nano calcium carbonate, and the dispersant of Example 8 is unmodified nano calcium carbonate, and polycaprolactone is added and directly mixed with all the raw materials. The results show that the dispersibility of Examples 7 and 8 is poor, and a small amount of white dots are precipitated in the migration resistance test, which leads to the poor dispersibility of the flame retardant in polyvinyl chloride, thereby reducing the flame retardant performance. This shows that choosing a suitable dispersant is very important to ensure the effective dispersion and effective flame retardancy of the flame retardant.
[0224] The various aspects, embodiments, and features of the present invention should be considered to be illustrative in all aspects and not limiting of the present invention, the scope of which is defined solely by the claims. Other embodiments, modifications, and uses will be apparent to those skilled in the art without departing from the spirit and scope of the claimed invention.
[0225] In the preparation method of the present invention, the order of each step is not limited to the order listed. For those skilled in the art, without creative work, the order of each step is also within the protection scope of the present invention. In addition, two or more steps or actions can be performed simultaneously.
[0226] Finally, it should be noted that the specific embodiments described herein are merely examples of the present invention, and are not intended to limit the implementation methods of the present invention. A person skilled in the art of the present invention may make various modifications or supplements to the specific embodiments described, or replace them in a similar manner. It is not necessary and impossible to provide all examples of all implementation methods here. However, these obvious changes or modifications derived from the essential spirit of the present invention still fall within the scope of protection of the present invention, and interpreting them as any additional limitation is contrary to the spirit of the present invention.
Claims
1. A highly dispersed flame retardant masterbatch, characterized in that: The invention comprises the following components in parts by weight: 8 to 30 parts of a high molecular polymer, 30 to 95 parts of a composite flame retardant, 6 to 20 parts of a plasticizer, and 0.1 to 15 parts of an auxiliary agent; the composite flame retardant comprises antimony trioxide, a borate, and an organic phosphorus-nitrogen complex, wherein the organic phosphorus-nitrogen complex is a mixture of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and melamine cyanurate, melamine phosphate, and ammonium polyphosphate or one or more thereof.
2. A highly dispersed flame retardant masterbatch according to claim 1, characterized in that: The composite flame retardant comprises a mixture of antimony trioxide, borate, and organic phosphorus-nitrogen complex in a mass ratio of 1:(0.5-1.0):(0.5-1.0); And / or, the organic phosphorus-nitrogen complex is a mixture of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and melamine cyanurate; And / or, the composite flame retardant includes antimony trioxide, borate, organic phosphorus-nitrogen complex and metal hydroxide.
3. A highly dispersed flame retardant masterbatch according to claim 1 or 2, characterized in that: The composite flame retardant comprises a mixture of antimony trioxide, borate, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and melamine cyanurate in a mass ratio of 1:(0.5-1.0):(0.3-0.6):(0.2-0.4).
4. The highly dispersed flame retardant masterbatch according to claim 1, characterized in that: The composite flame retardant comprises antimony trioxide, borate, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, melamine cyanurate and metal hydroxide; The mass of the metal hydroxide is 0.1 to 10 wt % of the total mass of the composite flame retardant; The metal hydroxide is aluminum hydroxide and / or magnesium hydroxide.
5. The highly dispersed flame retardant masterbatch according to claim 1, characterized in that: The borate is one or more of a metal salt of boric acid and a metal salt of fluoroboric acid, and the metal is one or more of sodium, potassium, magnesium, barium, ammonium, calcium, manganese, nickel, copper, aluminum, zinc, cobalt, and zirconium; And / or, the high molecular polymer is one or more of olefin polymer, ester polymer, vinyl polymer, styrene polymer, and polyurethane; And / or, the plasticizer is one or more of pyromellitic acid ester plasticizers, trimellitic acid ester plasticizers, phthalic acid ester plasticizers, terephthalic acid ester plasticizers, phosphate ester plasticizers, and epoxidized vegetable oil.
6. The highly dispersed flame retardant masterbatch according to claim 1, characterized in that: The borate is one or more of calcium borate, cobalt borate, anhydrous zinc borate, 3.5 hydrate zinc borate, sodium orthoborate, sodium perborate, sodium metaborate, sodium tetraborate, ammonium metaborate, ammonium pentaborate, calcium metaborate, barium metaborate, barium tetraborate, potassium metaborate, potassium tetraborate, potassium pentaborate, magnesium orthoborate, magnesium metaborate, trimagnesium tetraborate, pentamagnesium tetraborate, potassium tetrafluoroborate, sodium tetrafluoroborate, ammonium tetrafluoroborate, zinc tetrafluoroborate, calcium tetrafluoroborate, magnesium tetrafluoroborate, and barium metaborate; And / or, the high molecular polymer is one or more of polyvinyl chloride, chloroacetate resin, and ethylene-vinyl acetate copolymer; And / or, the plasticizer is one or more of dioctyl phthalate, dinonyl phthalate, diisodecyl phthalate, diundecyl phthalate, didodecyl phthalate, ditridecyl phthalate, dioctyl terephthalate, tri(isopropylphenyl) phosphate, dialkyl tetrahalophthalate, tri(2-chloroethyl) phosphate, bisphenol A-bis(diphenyl phosphate), and epoxidized soybean oil.
7. The highly dispersed flame retardant masterbatch according to claim 1, characterized in that: The auxiliary agent includes one or more of a dispersant, a stabilizer, and a lubricant; The dispersant is polycaprolactone modified nano calcium carbonate, and the amount of the dispersant is 0.1 to 4 parts; The stabilizer is a liquid calcium zinc stabilizer and a powder calcium zinc stabilizer, and the stabilizer is 0.5 to 6.0 parts; The lubricant includes one or more of metal soap lubricants, hydrocarbon lubricants, fatty acid lubricants, and fatty acid ester lubricants, and the lubricant is 0.1 to 3 parts.
8. The highly dispersed flame retardant masterbatch according to claim 7, characterized in that: The preparation method of the polycaprolactone modified nano calcium carbonate comprises the following steps: The nano-calcium carbonate and polycaprolactone are put into a high-speed mixer and mixed, the temperature is raised to 70-100° C. within 5-20 minutes, the mixture is kept warm and stirred for 5-60 minutes, the mixture is discharged, and after cooling, the polycaprolactone-modified nano-calcium carbonate is obtained.
9. A highly dispersed flame retardant masterbatch according to claim 8, characterized in that: The average particle size of nano calcium carbonate is 10 to 999 nm; And / or, the mass of polycaprolactone is 0.5-15wt% of the mass of nano-calcium carbonate; And / or, the rotation speed of the high-speed mixer is 500 to 10,000 rpm.
10. The method for preparing a highly dispersed flame retardant masterbatch according to claim 1, characterized in that: The following steps are involved: Weigh each component of the high-dispersion flame-retardant masterbatch, add it into a mixing tank at 100-180°C and mix it for 5-50 minutes, transfer it into a three-roll grinder for grinding and dispersion, and then press the ground and dispersed material through a double-roller machine, and cut it with a cutting machine to obtain a cake-shaped high-dispersion flame-retardant masterbatch.
Citation Information
Cited By
High-dispersion flame-retardant antistatic ABS (Acrylonitrile Butadiene Styrene) masterbatch and preparation method thereof
CN122325926A